The Alleviation of Heat Damage to Photosystem II and Enzymatic Antioxidants by Exogenous Spermidine in Tall Fescue - Zhang, Liang; Hu, Tao; Amombo, Erick; Wang, Guangyang; Xie, Yan; Fu, Jinmin (Frontiers in Plant Science, 2017)
Tall fescue (Festuca arundinacea Schreb) is a typical cool-season grass that is widely used in turf and pasture. However, high temperature as an abiotic stress seriously affects its utilization. The objective of this study was to explore the effect of spermidine (Spd) on heat stress response of tall fescue. The samples were exposed to 22 ºC (normal condition) or 44 ºC (heat stress) for 4 hours. The results showed that exogenous Spd partially improved the quality tall fescue leaves under normal temperature conditions. Nevertheless, after heat stress treatment, exogenous Spd significantly decreased the electrolyte leakage (EL) of tall fescue leaves. Spd also profoundly reduced the H2O2 and O2•- content and increased antioxidant enzymes activities. In addition, PAs can also regulate antioxidant enzymes activities including SOD, POD, and APX which could help to scavenge ROS. Moreover, application of Spd could also remarkably increase the chlorophyll content and had a positive effect on the chlorophyll α fluorescence transients under high temperature. The Spd reagent enhanced the performance of photosystem II (PSII) as observed by the JIP-test. Under heat stress, the Spd profoundly improved the partial potentials at the steps of energy bifurcations (PIABS and PItotal) and the quantum yields and efficiencies (φP0, δR0, φR0, and γRC). Exogenous Spd could also reduce the specific energy fluxes per QA- reducing PSII reaction center (RC) (TP0/RC and ET0/RC). Additionally, exogenous Spd improved the expression level of psbA and psbB, which encoded the proteins of PSII core reaction center complex. We infer that PAs can stabilize the structure of nucleic acids and protect RNA from the degradation of ribonuclease. In brief, our study indicates that exogenous Spd enhances the heat tolerance of tall fescue by maintaining cell membrane stability, increasing antioxidant enzymes activities, improving PSII, and relevant gene expression.